Respuesta :

RNcyx

Answer:

(59-6) × [tex]\sf{(\frac{1}{3})}^{3}[/tex] + 27 ÷ 3

=53 × [tex]\sf\frac{{1}^{3}}{{3}^{3}}[/tex] + 3³ ÷ 3

=53 × [tex]\sf\frac{1}{27}[/tex] + [tex]\sf{3}^{3-1}[/tex]

=[tex]\sf\frac{53\times1}{27}[/tex] + [tex]\sf{3}^{2}[/tex]

=[tex]\sf\frac{53}{27}[/tex] + 9

=9 + [tex]\sf\frac{53}{27}[/tex] + 9

=[tex]\sf\frac{9\times27+53}{27}[/tex]

=[tex]\sf\frac{243+53}{27}[/tex]

=[tex]\sf\frac{296}{27}[/tex]

=[tex]\sf\frac{270}{27}+\frac{26}{27}[/tex]

=[tex]\sf10+\frac{26}{27}[/tex]

=[tex]\sf10\frac{26}{27}[/tex]

[tex]\sf\:[/tex]

8² ÷ 4 × (2 + 3) - 9

=(8×8) ÷ 4 × 5 - 9

=64 ÷ 4 × 5 - 9

=4³ ÷ 4 × 5 - 9

=[tex]\sf{4}^{3-1}[/tex] × 5 - 9

=4² × 5 - 9

=(4×4) × 5 - 9

=16 × 5 - 9

=80 - 9

=71